Аналіз показників розумової та фізичної працездатності в жінок-курців - Апончук, Людмила; Шевчук, Тетяна; Бернацька, Ніна; Aponchuk, Ludmyla; Bernats’ka, Nina; Shevchuk, Tetyana (Східноєвропейський національний університет імені Лесі Українки, 2015)
Проаналізовано та вивчено особливості стану показників розумової й фізичної працездатності в жінок- курців. Установлено, що в них рівень фізичної працездатності за визначенням індексу гарвардського степ- тесту відповідає слабкому (І група) та середньому (ІІ група), що вказує на низький рівень функціонального стану серцево-судинної системи обстежуваних осіб. Дослідження розумової працездатності засвідчило, що в жінок-курців І й ІІ груп показник розумової працездатності відповідає низькому рівню за шкалою оцінювання, що пояснюється згубною дією тривалого куріння на нервову систему, поступове зниження уваги, пам’яті, працездатності, ефективності засвоєння нових знань. Specific indicators of the state of mental and physical ability of female smokers were studied and analyzed. It was established that according to the Harvard step test, female smokers’ physical ability meets low (group 1) and medium (group 2) levels, which indicates a low level of functional state of the cardiovascular system of the examinees and accordingly this affects negatively the adaptation to physical activity and increases the tone of the sympathetic nervous system. Studies of mental capacity showed that among female smokers of group 1 and 2 the indicator of mental capacity corresponds to low-level scale of assessment. This may be explained by the fact that long- term smoking has a detrimental effect on the nervous system; it gradually reduces attention, memory, performance, efficiency and assimilation of new knowledge and as a result deterioration of mental activity (reduced accuracy of perception) is observed.
Analysis of Mental and Physical Capacity of Female Smokers
Keywords: розумова працездатність; тютюнопаління; жінки; фізична працездатність; mental performance; women; smoking; physical performance